Kvantitativ RT-PCR-analys för detektion av pigmentrelaterade transkript i hårrötter från hund - Falkenö, Ulrika (2008)
Malignant melanoma represents 4-7% of all canine neoplasms and they are the most common malignant tumors of the oral cavity and digits. These tumors are often aggressive and metastasize quickly. To date there is no effective treatment and survival times are short. Most dogs are euthanized due to complications caused by metastases. Melanin pigment is a hallmark of melanomas and is usually present in large amounts in these tumors. The aim of this study was to see if quantitative reverse transcriptase-polymerase chain reaction (QRT-PCR) could be used for detection of pigment related transcripts in canine hair roots. Human primers and probes were used for tyrosinase (TYR) and tyrosinase related protein 1 (TYRP1). For antigen recognized by T cells 1 (Melan-A/MART1) probe and primers had to be redesigned to fit the canine genome. The samples consisted of 30 hair roots each from 18 dogs with different fur colour. Our results show that black hair has a large amount of the pigment related transcripts and that white hair has no or very little TYR and TYRP-1 transcripts. Even brown and yellow hair roots contain no or very little TYR and TYRP-1 transcripts. In the future it would be interesting to analyze the pigment content of canine hair of especially brown and yellow color. If developed for analysis of the pigment related transcripts in tumour and lymphatic tissue as well as in blood this quantitative RT-PCR method could be usable for detection of melanomas, staging of patients and monitoring of therapeutic effect in both humans and dogs.